2014
DOI: 10.7860/jcdr/2014/8101.4906
|View full text |Cite
|
Sign up to set email alerts
|

Is Low Dose Vaginal Misoprostol Better Than Dinoprostone Gel For Induction of Labor: A Randomized Controlled Trial

Abstract: Objective: To compare the efficacy and safety profile of low dose vaginal misoprostol with dinoprostone gel for induction of labor in term pregnancies. Methods:The study was conducted at Lady Hardinge Medical College and Smt Sucheta Kriplani Hospital on 100 pregnant women with term pregnancy after application of inclusion and exclusion criteria. The women were randomized in 2 groups of 50 women each. Group I received misoprostol 25µg at every six hour vaginally for a maximum of five doses for induction of labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 8 publications
2
9
1
1
Order By: Relevance
“…Despite the confirmed effectiveness of misoprostol in labor pre-induction, there considerations regarding risk of causing tachysystole, hyperstimulation, meconium-stained fluids or cardiotocographic abnormalities [8,17,18,[22][23][24]29]. In our study we recorded only 2% of cases with tachysystoly, same for hyperstimulation.…”
Section: %mentioning
confidence: 61%
See 3 more Smart Citations
“…Despite the confirmed effectiveness of misoprostol in labor pre-induction, there considerations regarding risk of causing tachysystole, hyperstimulation, meconium-stained fluids or cardiotocographic abnormalities [8,17,18,[22][23][24]29]. In our study we recorded only 2% of cases with tachysystoly, same for hyperstimulation.…”
Section: %mentioning
confidence: 61%
“…The most common extra drugs used in our study were oxytocin (56% of cases) and Fenoterol (19% of cases), both used more commonly in primigravidas. There are many studies confirming a less frequent use of drugs in the setting of MVI [3,10,14,17,20,23]. Since the rate of deliveries in our clinic was high, duration of hospitalization was short and all our patients were discharged within 2-4 days.…”
Section: %mentioning
confidence: 79%
See 2 more Smart Citations
“…This study found no differences between both methods. However, because of a limited sample size (50 patients for each group), there may not have been enough statistical power to detect differences …”
Section: Discussionmentioning
confidence: 99%